Impact of NPEGEL on Girls’ Education at Elementary Level in Tribal District of Odisha - Roul, Kartikeshwar (JOURNAL OF INDIAN EDUCATION, 2011)
A number of affirmative activities are undertaken and also proposed under Sarva Shiksha Abhiyan (SSA) to deepen gender awareness and to enhance girls access, enrolment and retention in the school system. These activities can broadly be classified into some broad heads like creating the right environment, improving the reach, ensuring entry into school, ensuring retention, installing gender equity and towards better learning. National programme for education of girls at elementary level (NPEGEL) is an integral part of SSA specially concentrates on girls education in educationally backward block and SC/ST blocks of India. This article has made an attempt to focus on various interventions of NPEGEL programme for development of girls education and its positive effects/impact in achieving universal elementary education (UEE) specially in tribal district of Odisha.